Mobile Camera as a Human Vision in Augmented Reality - Edmund Ng Gaip Weng; Rehman Ullah Khan; Shahren Ahmad Zaidi Adruce; Oon Yin Bee (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The real world objects can be recognized by using marker based and marker-less augmented reality systems. Mostly, the previous developers used markers based augmented reality systems. However, those systems actually hide the reality and it was also difficult to keep the markers everywhere. Furthermore, the previous marker-less approaches use client-server architecture, which is drastically affected by network latency. Smartphone camera is matured enough that it can recognize real world objects without markers. It can guide users about their location and the direction in a convenient way. The use of Smartphone is best suited for outdoor mobile augmented-reality applications. Therefore, a marker-less natural features based tracking system in mobile augmented reality was formulated. In the adapted framework, the state-of-the-art algorithm (speed up robust features) was modified for computing image features from live mobile camera image and compares with locally stored images features for recognition. Moreover, the local static database of location tagged image features using SQLite was implemented to bypass the server. The proposed system was tested in a mobile AR-prototype application using iPhone called UNIMAS Guide. It was found from the results that the adapted marker-less system could recognize the real world objects in speedy, easy and convenient way. This technology can be applied in tourism industry, surgery and educational fields. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2798